Kobeko Learning Model based Web Blog (High education ballad amid the siege of Covid-19): Model Pembelajaran Kobeko Berbasis Web Blog (Balada Pendidikan Tinggi di Tengah Kepungan Wabah Covid-19) - Siti Osa Kosassy (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
One of the hot topics that continues to be discussed today is the change in the learning process where from face to face in school to